Peranan Kompetensi Auditor Memoderasi Pengalaman Kerja Dan Independensi Auditor Terhadap Kualitas Audit Pada KAP Medan - Azwar, Khairul; Wirananda, Henny Andriyani; Susanti, Elly; Ervina, Nelly (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2023)
The purpose of this study is to find out and analyze whether the auditor's competence is able to moderate the auditor's experience and auditor's independence on audit quality at KAP Medan. The type of research used is quantitative using primary data. The population in this study was auditors from KAP Drs. Katio &; Rekan, KAP Drs Syamsul Bahri, MM, Ak &; Rekan, KAP Fachrudin & Mahyuddin, and KAP Johannes Juara &; Rekan as many as 30 people. The sample in this study is a saturated sample, that is, all members of the population will be used as samples. F test results show that work experience and auditor independence have a positive and significant effect on audit quality. The results showed that audit experience had a positive and significant effect on audit quality. This means that the more experience and knowledge the auditor has, the more relevant and reliable audit quality will result. Audit independence has a positive and insignificant effect on audit quality. This means that the auditor has a weak independent mental attitude and loss of auditor independence because the auditor has a tendency to satisfy his clients and is afraid of losing his clients as well as financial interests and business relationships with clients. The study also found that auditor competence was unable to moderate work experience and auditor independence on audit quality.